Mechanical and deformation properties of rubberized engineered cementitious composite (ECC). (December 2020) - Alaloul, Wesam Salah; Musarat, Muhammad Ali; A Tayeh, Bassam; Sivalingam, Sarvesh; Rosli, Mohd Faridzuan Bin; Haruna, Sani; Khan, Muhmmad Imran
Abstract: The production of scrap rubber tyres is burgeoning at an alarming rate. Compared to toxic disposal methods that leave a trail of environmental issues, using scrap rubber tyres as a partial aggregate replacement in materials such as bitumen and concrete will address the heightening environmental effects. The usage of crumb rubber as partial fine aggregate replacement in Engineered Cementitious Concrete (ECC) is a sprouting new technique under many critiques and scientific analysis. This study encompasses a comprehensive investigation of the crumb rubber incorporated ECC in terms of its compressive strength, flexural strength, direct tensile strength, and deflection abilities by adding crumb rubber content as a replacement of fine aggregate, Polyvinyl Alcohol (PVA) and superplasticizers. Various mix designs were calculated by inputting the values into a Research Surface Methodology (RSM) to obtain a model for the optimal crumb rubber and PVA volumes to verify reliability. The results from the study revealed that crumb rubber reduced the compressive strength of the concrete, increased the flexural and tensile behaviour, shrinkage content, possessed a low modulus of elasticity, and high value of the Poisson's ratio. Finally, the relationship between independent factors and dependent responses were evaluated using ANOVA analysis and the models were found to be significant.